The aetiology of dry socket: a review - Awang, M.N. (Wiley, 1989)
The aetiology of dry socket continues to be the subject of intense research. Local disturbances of fibrinolytic activity appear to be the most satisfactory explanation for the pathogenesis of this disorder. The factors that are responsible for local changes in fibrinolytic activity are reviewed and evaluated. In the management of this disorder attention should be directed towards the prevention of local changes in fibrinolytic activity.